2010
DOI: 10.1007/s00105-010-1979-7
|View full text |Cite
|
Sign up to set email alerts
|

Exulcerated, nodular tumor on the occiput of a 29-year-old patient

Abstract: Cranial fasciitis is a rare variation of nodular fasciitis that occurs in the region of the capillitium. We report on a 29-year-old patient who presented with a 2-month history of a tumor progressively increasing in size located on the occiput. Histological examination revealed a tumor, consisting of tightly packed spindle-shaped cells with underlying myxoid stroma, which extended from the dermis to the subcutis. Actin and vimentin were detected by immunohistochemistry. We established a diagnosis of cranial fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In all the cases, nodular fasciitis presented as a unique, well‐circumscribed and non‐tender mass with a size that may vary between 5 mm and 88 mm. In 14 out of the 53 articles, the authors specified the nodular fasciitis subtype identifying: 5 cases of subcutaneous fasciitis, 7,10,27–29 4 cases of cranial fasciitis, 14,22,23,30,31 3 cases of intravascular fasciitis, 8,32,33 1 case of periosteal fasciitis 34 and 1 case of subepithelial myxoid fasciitis 35 . A total of 151 patients were asymptomatic, 3 suffered from pain 36 and 11 suffered from accessory symptoms, like diplopia, blurred vision, trismus, dyspnoea, proptosis, fever, masticatory deficiency and otorrhoea 2,4,19,26,31,33,36–40 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all the cases, nodular fasciitis presented as a unique, well‐circumscribed and non‐tender mass with a size that may vary between 5 mm and 88 mm. In 14 out of the 53 articles, the authors specified the nodular fasciitis subtype identifying: 5 cases of subcutaneous fasciitis, 7,10,27–29 4 cases of cranial fasciitis, 14,22,23,30,31 3 cases of intravascular fasciitis, 8,32,33 1 case of periosteal fasciitis 34 and 1 case of subepithelial myxoid fasciitis 35 . A total of 151 patients were asymptomatic, 3 suffered from pain 36 and 11 suffered from accessory symptoms, like diplopia, blurred vision, trismus, dyspnoea, proptosis, fever, masticatory deficiency and otorrhoea 2,4,19,26,31,33,36–40 …”
Section: Discussionmentioning
confidence: 99%
“…The nodular fasciitis diagnosis was generally based on a CT scan, sometimes associated with an MRI scan, ultrasound image and/or incisional biopsy. The gold standard therapy is surgical resection as documented by the literature 1,2,5–59 . In five cases, the authors preferred a wait‐and‐see approach, 3,11,60,61 while in another seven cases, the authors reported a spontaneous regression of the pathology 42 .…”
Section: Discussionmentioning
confidence: 99%